The Influence of Housing Loan (KPR) to Non Performing Loan and its Impact on Return on Asset (Case Study on PT. Bank Tabungan Negara (Persero) Tbk.) - Kusnandar, Hasan Fahmi; Sulaeman, Maman; Gunawan, Gun Gun; Debara, Rangga Puja (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2019)
The purpose of this research is to know a housing loan, non performing loan and return on asset as well as the influence of housing loan on non performing loan, and to determine the influence of housing loan and non performing loan are either partially or simultaneously on return on asset at PT. Bank Tabungan Negara (Persero) Tbk. The method used in this research is descriptive method analysis with aproach a case study to the PT. Bank Tabungan Negara (Persero) Tbk. The data collected form the primary data and secondary data with analysis technique using path analysis. The results showed that : (1) a housing loan on PT. Bank Tabungan Negara (Persero) Tbk. shows the biggest result in the year 2015, non performing loan on PT. Bank Tabungan Negara (Persero) Tbk. shows the biggest result in the year 2012 until year 2015 and return on asset on PT. Bank Tabungan Negara (Persero) Tbk. shows the biggest result in the year 2010 (2) housing loan significant effect on non performing loan (3)  housing laon in partial does effect significant to return on asset,  partial non performing loan does not effect significant to return on asset and housing loan and simultaneous non performing loang does effect significant on return on asset.